THE COPYRIGHT IN THE INFORMATION SOCIETY - Cristinel Ioan MURZEA (Challenges of the Knowledge Society)
The contemporary society has imposed new demands in the development and application of copyright as a result of structural changes which occur as a result of developments in science, technology and especially communication technologies and of informatics. Legal doctrine highlights axiomatic truth according to which the “environment created by technological developments” brings forward the profound informational dimension of human being in the contemporary society. In this context the integration and the harmonization of legislation of the Member States of the European Union leads to a complex and dynamic process by which the copyright called to legally protect intellectual creation in contemporary society, acquires a universal vocation in the contemporary society, because there are no barriers or impediments in its spreading especially due to the phenomenon of multiplication and improvement of means of information and communication